2021
DOI: 10.17269/s41997-021-00522-7
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining spaces where children play: developing guidance for thermally comfortable playgrounds in Canada

Abstract: Setting Planning and designing thermally comfortable outdoor spaces is increasingly important in the context of climate change, particularly as children are more vulnerable than adults to environmental extremes. However, existing playground standards focus on equipment and surfacing to reduce acute injuries, with no mention of potential negative health consequences related to heat illness, sun exposure, and other thermal extremes. The goal of this project was to develop proposed guidelines for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Mahé et al [28] explored the risk of ultraviolet radiation-induced skin damage during outdoor sports and recommended that children take appropriate sun protection measures. Kennedy et al [29] developed guidelines for thermal comfort on Canadian playgrounds. The results suggest that thermally safe and comfortable playgrounds minimize environmental health risks for children.…”
Section: Introductionmentioning
confidence: 99%
“…Mahé et al [28] explored the risk of ultraviolet radiation-induced skin damage during outdoor sports and recommended that children take appropriate sun protection measures. Kennedy et al [29] developed guidelines for thermal comfort on Canadian playgrounds. The results suggest that thermally safe and comfortable playgrounds minimize environmental health risks for children.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding age, studies have indicated that the elderly have poorer adaptation to changes in thermal environments, particularly during cold spells [260] or heatwaves [261]. Additionally, children are more vulnerable to the impact of extreme climate conditions outdoors compared to adults [262]. For people with disabilities, individuals with physical impairments may have different heat adaptation responses under extreme climate conditions compared to those without disabilities.…”
Section: Human Health Assessment and Prediction Based On Outdoor Ther...mentioning
confidence: 99%
“…Ideally, it should also facilitate accurate shade design specific to a given location. Such a tool can be valuable to designers in building new or retrofitting playgrounds, as sun and heat protection are often overlooked, yet are important design aspects of such areas (20).…”
Section: Introductionmentioning
confidence: 99%
“…Playgrounds within a parkland are environments exposed to the sun at all times of the year. They can therefore place visitors at risk of thermal stress and excessive sun exposure (10). Shading provided by trees, vegetation and physical shade structures is important (2,8,11), as behaviors when young (12) influence lifetime exposure patterns to solar ultraviolet (UV) radiation; that in turn contributes to the development of harmful skin and eye disease (13).…”
Section: Introductionmentioning
confidence: 99%